ANALISIS ETOS BELAJAR SAAT PANDEMI COVID 19 PADA MATA PELAJARAN IPS PESERTA DIDIK KELAS VIII A SMP NEGERI 3 SUNGAI RAYA KABUPATEN KUBU RAYA - Vendra Yudistira; Mashudi Mashudi; Aminuyati Aminuyati (Universitas Tanjungpura, 2022)
AbstractThis study aims to identify the learning ethos of students during the Covid-19pandemic in the form of learning characteristics and study habits in socialstudies subjects for class VIII A students at SMP Negeri 3 Sungai Raya, KubuRaya Regency. The research method used in this study is qualitative, with datasourced from class VIII A students and social studies subject teachers (primary)as well as documentation of learning activities. Data collection techniques usedwere observation, interviews, and documentation. The result of the study showthat due to the Covid-19 virus which forces students to study at home, it has animpact on the learning ethos of students. The learning ethos of class VIII Astudents is in the good category, with four indicators of the characteristics ofthe learning ethos, two of which are in students, namely reading interest andlearning responsibility, while learning independence and courage to facechallenges are still lacking. While studying at home, the study habits of studentsare also good with a supportive learning place, sufficient study time, astructured study schedule and a system for doing assignments without delay.Keywords : Covid-19, Learning Ethos, Social Studies Lesson